If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8y = -9 + 7y Solving 8y = -9 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. 8y + -7y = -9 + 7y + -7y Combine like terms: 8y + -7y = 1y 1y = -9 + 7y + -7y Combine like terms: 7y + -7y = 0 1y = -9 + 0 1y = -9 Divide each side by '1'. y = -9 Simplifying y = -9
| 30=.36/x | | 2(x+5)-2=-(2x+1)+x | | 15=x/6-1 | | .5x^2-12.5=75 | | -28-(1/4 | | 3e-19=2(e+2) | | 72=0.5(3x+6)(x+4) | | 2(-16-8y)=64 | | Y=5-2(1) | | 5c=4c-7 | | 8+7(x-6)=9-7(x-6) | | y-9=1/3(x-5) | | Y=5-2(2) | | 6x+5+5x=-28 | | 3(7)+4y=34 | | 20y+12x=20 | | 2.25x+12=39 | | 4a-3a-a+3a-a=20 | | X(x-6)+16=0 | | 3(-2)+y=2 | | 8h+7h+15h-13h-4h=13 | | 3(3.44a+3)+6=87 | | 7x-(3x+11)=17 | | 15y-14y-y+y-1=10 | | 4/5-4=2/3p | | 10(x-2)-10forx=15 | | 5/2x=17.5 | | 105=0.5(x+2)(3x+15) | | -3(2x+1)+4=11 | | -2+2x=-x+2+c | | -5+2.3=18.8 | | 12p-3p-8p=-5 |